Densitas Kamba Jagung Hibrida Pertiwi Kabupaten Sidenreng Rappang - Salfiana Salfiana; Rismawati . (Journal Of Agritech Science (JASc), 2021)
The aim of this research was to measure or quantitatively identify the Bulk Density Of Pertiwi Hybrid Corn Sidenreng Rappang Regency. Determination of bulk density is done by calculating the mass of corn kernels per volume occupied including the empty space between the corn kernels. The results of the calculation obtained that the Bulk Density Of Pertiwi Hybrid Corn Sidenreng Rappang Regency was in the range of 705-745 Kg/m3.